CORAL FACIES AND CYCLICITY IN THE CASTELGOMBERTO LIMESTONE (Early Oligocene, Eastern Lessini Mountains, Northern Italy) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1992)
The Castelgomberto Limestone is a 2OO m thick unit of Early Oligocene age (Rupelian) outcropping in the Eastern Lessini Mountains (Southern Alps of Northern ltaly). The internal cyclic organization of this Oligocene unit is described and analyzed on the basis of four selected sections; about thirteen well-bedded grainstone units alternate with marly horizons rich in corals. This peculiar cyclicity is here interpreted as a response to variations in platform hydrodynamics, i. e. to smaller eustatic fluctuations affecting the Lessini Shelf reef-lagoonal complex. During highstand periods, the shelf was open and relatively deep (20-50 m), and tidal currents and periodic storms were able to distribute bioclastic sands (bars, sand waves and spillovers). During lowstands the shelf was more protected by the occurrence of marginal reefs and was colonized by patches of poritid corals, mainly branching. Moreover, the largely exposed northern areas supplied fine detritus to the shelf itself.
Keywords: Stratigraphy; Cycles; Facies; Corals; Early Oligocene; Lessini Mountains (Northern Italy).